2015
DOI: 10.1097/ico.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis Comparing the Preoperative and Postoperative “Q” Values for 2 Different Lasers in Refractive Surgery

Abstract: Low to moderate myopic correction with the Allegretto laser was associated with a smaller change in the Q value per diopter of treatment and therefore more closely maintained the original prolate shape of the cornea when compared with VISX. No difference in the postoperative visual outcome between both groups was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…However, Moshirfar et al [ 4 ], Khalifa et al [ 21 ], and Ghoneim et al [ 31 ] found that the level of induced HOAs was significantly higher in the WFO group than in the WFG group, which could be attributed to their use of high-resolution aberrometer measurements to define WFG ablation profiles [ 4 , 21 , 31 ]. Concerning the change in corneal asphericity, our results were similar to those of Bottos et al [ 33 ] and Molchan et al [ 34 ], where ΔQ was significantly greater in the WFG group than in the WFO group ( P = 0.034). The mean maximal laser ablation depth in our study was greater in the WFG group than in the WFO group ( P = 0.035).…”
Section: Discussionsupporting
confidence: 91%
“…However, Moshirfar et al [ 4 ], Khalifa et al [ 21 ], and Ghoneim et al [ 31 ] found that the level of induced HOAs was significantly higher in the WFO group than in the WFG group, which could be attributed to their use of high-resolution aberrometer measurements to define WFG ablation profiles [ 4 , 21 , 31 ]. Concerning the change in corneal asphericity, our results were similar to those of Bottos et al [ 33 ] and Molchan et al [ 34 ], where ΔQ was significantly greater in the WFG group than in the WFO group ( P = 0.034). The mean maximal laser ablation depth in our study was greater in the WFG group than in the WFO group ( P = 0.035).…”
Section: Discussionsupporting
confidence: 91%
“…7 Molchan et al demonstrated a smaller change in corneal asphericity per diopter of treatment with myopic correction using the Allegretto wavefront-optimized laser when compared to the VISX wavefront-guided laser for refractive surgery. 8 Lee and Lee demonstrated the WaveLight Refractive Suite, consisting of the femtosecond laser FS200 and WaveLight EX500 excimer laser, offers good refractive predictability in LASIK procedures. 9 At present, no studies have compared the induced aberrations postoperatively between the VISX Star S4 IR Excimer Laser System (Abbott Medical Optics, Santa Ana, California) and WaveLight EX500 Excimer Laser System (Alcon, Fort Worth, Texas).…”
Section: Introductionmentioning
confidence: 99%
“…Bottos et al [ 15 ] reported that the mean +Δ Q was +0.63 ± 0.44 after wavefront-guided LASIK using a femtosecond flap. Molchan et al [ 16 ] found that the mean +Δ Q was +0.39 ± 0.20 after wavefront-optimized LASIK and +0.54 ± 0.26 after wavefront-guided LASIK using PRK. El Danasoury et al [ 17 ] found that the mean Q -value was +0.07 ± 0.26 after LASIK with an optimized prolate ablation (OPA) and +0.30 ± 0.26 after LASIK with conventional ablation using a femtosecond flap.…”
Section: Discussionmentioning
confidence: 99%
“…Bottos et al [ 15 ] reported that Δ Q per diopter of treatment SE was +0.18 after wavefront-guided LASIK. Molchan et al [ 16 ] found that Δ Q per diopter of treatment SE was +0.12 after wavefront-optimized LASIK and +0.14 after wavefront-guided LASIK. Vega-Estrada et al [ 20 ] reported that, for each diopter of spherical correction, asphericity (8 mm) increased by 0.223 postoperatively in high myopic eyes after LASIK performed with an optimized ablation profile.…”
Section: Discussionmentioning
confidence: 99%